Non‐invasive evaluation of new‐onset atrial fibrillation after cardiac surgery: a protocol for the BigMap study. (19th April 2022) - Mork, Constantin; Amacher, Simon Adrian; Gahl, Brigitta; Koechlin, Luca; Miazza, Jules; Schaeffer, Thibault; Schmuelling, Lena; Bremerich, Jens; Berdajs, Denis; Cueni, Nadine; Kühne, Michael; Mueller, Christian; et al.
Abstract: Aims: New‐onset atrial fibrillation (NOAF) is the most common complication after cardiac surgery, occurring in 25–50% of patients. It is associated with post‐operative stroke, increased mortality, prolonged hospital length of stay, and higher treatment costs. Previous small observational studies have identified the left atrium as a source of the electrical rotors and foci maintaining NOAF, but confirmation by a large prospective clinical study is still missing. The aim of the proposed study is to investigate whether the source of NOAF lies in the left atrium. The correct identification of NOAF‐maintaining structures in cardiac surgical patients might offer potential therapeutic targets for prophylactic perioperative ablation strategies. Methods and results: This is a prospective single‐centre observational study of patients developing NOAF after cardiac surgery. The primary outcome is the description of NOAF‐maintaining structures within the atria. Key secondary outcomes include overall mortality, intensive care unit length of stay, hospital–ventilator‐free days, and proportion of persistent NOAF. In NOAF patients, the non‐invasive electrophysiological mapping will be conducted using a 252‐electrode electrocardiogram vest. After mapping, a low‐dose computed tomography scan of the chest will be performed to integrate the electrophysiological mapping results into a 3D picture of the heart. The study will include approximately 570 patients, of whom 30% ( n = 170) are expected to develop NOAF. Sample size calculation revealed that 157 NOAF patients are necessary to assess the primary outcome. Patients will be tracked for a total of 5 years. Conclusions: This is the largest prospective study to date describing the electrophysiological mechanisms of NOAF using non‐invasive mapping.